If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (50 + X)(75 + 2X) = 9375 Multiply (50 + X) * (75 + 2X) (50(75 + 2X) + X(75 + 2X)) = 9375 ((75 * 50 + 2X * 50) + X(75 + 2X)) = 9375 ((3750 + 100X) + X(75 + 2X)) = 9375 (3750 + 100X + (75 * X + 2X * X)) = 9375 (3750 + 100X + (75X + 2X2)) = 9375 Combine like terms: 100X + 75X = 175X (3750 + 175X + 2X2) = 9375 Solving 3750 + 175X + 2X2 = 9375 Solving for variable 'X'. Reorder the terms: 3750 + -9375 + 175X + 2X2 = 9375 + -9375 Combine like terms: 3750 + -9375 = -5625 -5625 + 175X + 2X2 = 9375 + -9375 Combine like terms: 9375 + -9375 = 0 -5625 + 175X + 2X2 = 0 Factor a trinomial. (-225 + -2X)(25 + -1X) = 0Subproblem 1
Set the factor '(-225 + -2X)' equal to zero and attempt to solve: Simplifying -225 + -2X = 0 Solving -225 + -2X = 0 Move all terms containing X to the left, all other terms to the right. Add '225' to each side of the equation. -225 + 225 + -2X = 0 + 225 Combine like terms: -225 + 225 = 0 0 + -2X = 0 + 225 -2X = 0 + 225 Combine like terms: 0 + 225 = 225 -2X = 225 Divide each side by '-2'. X = -112.5 Simplifying X = -112.5Subproblem 2
Set the factor '(25 + -1X)' equal to zero and attempt to solve: Simplifying 25 + -1X = 0 Solving 25 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -1X = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -1X = 0 + -25 -1X = 0 + -25 Combine like terms: 0 + -25 = -25 -1X = -25 Divide each side by '-1'. X = 25 Simplifying X = 25Solution
X = {-112.5, 25}
| n-4=-15 | | 1130-720f=382 | | 40-80d=c | | 3+1+x=12 | | 2(x-7)-10=12-4x | | 2(8+2x)= | | 28+2=n+22 | | 0=-18+v | | 3m^2+8m+15= | | 2b-10+17+5b=7-10-5b+2b | | 10-4(4)=-x | | 16f-7f-2f= | | 2=2k+3k^2 | | -8x-14=3x-7(x-2) | | 19g-18g=7 | | 4(-10+4y)-4y=8 | | 6y+15-8y=1 | | 2a=5+1 | | 10+9=n+17 | | 5(3x-2)=12 | | 245-310t=2105 | | 14c-12c=16 | | k-30=-13 | | 3b-5+8+6b=4-10-4b+2b | | 4-5z+8z+8+7z=132 | | 3v-3(v+12)=6(3+3v) | | -1-2p+5=4p+6 | | 2x-5+3=-18 | | 2(x+3)+8=-18 | | 25x+9.95=259.95 | | (x-20)=(4x+15) | | 29.75+0.15=19.95+0.29 |